The complete chloroplast genome sequence of Nostolachma jenkinsii (Hook.f.) Deb & J.Lahiri, an endangered coffeeae plant - Wenshuai Chen; Guanfei Zhao; Ming Lei; Rongjie Zhu (Mitochondrial DNA. Part B. Resources, 2024)
Nostolachma jenkinsii (Hook.f.) Deb & J.Lahiri, a member of the Rubiaceae family, is an endangered wild plant species with potential economic value. In this research, the complete chloroplast genome of N. jenkinsii was sequenced to gain insight into its genome feature and better understand the phylogenetic relationships among the Rubiaceae species. The chloroplast genome, with a total length of 155,036 bp, comprises two inverted repeats (IR) regions spanning 25,692 bp each, a large single-copy (LSC) region measuring 85,437 bp, and a short single-copy (SSC) region measuring 18,215 bp. There is an overall 37% GC content in the chloroplast genome. By annotation analysis,. 54 tRNA genes, 10 rRNA genes, and 107 protein-coding genes were all annotated in N. jenkinsii. Furthermore, we applied phylogenetic analysis that revealed a close relationship between N. jenkinsii, D. fruticosa and D. dubia, placing them together within the Rubiaceae family.